Perancangan Sistem Labeling ODP (Optical Distribution Point) Berbasis Web di PT. Telkom Akses Balikpapan - Abdi Muhyiddin; Mayda Waruni Kasrani; Anwar Fattah (Lembaga Penelitian Universitas Balikpapan, 2024)
PT. Telkom Akses has an assurance division whose job is to carry out preventive maintenance on the Indihome network and handle problems directly with the TTR (Time To Repair) concept of < 3 hours. However, in handling disruptions, technicians often encounter obstacles regarding invalid ODP data and customer data, which makes the work of assurance technicians less efficient. To overcome this problem, efforts were made to create an ODP label system which contains information regarding ODP status and customer data. This research uses the waterfall design method which focuses on development using UML (Unified Model language) and using the PHP programming language, as well as Xampp with Apache as the web server. and MySQL which is used as database storage. So this research produces an application that can make it easier for technicians to search for customer data. Based on the test results, the web-based Optical Distribution Point (ODP) labeling system has met the expected usability aspects. Testing has been carried out using the functional blackbox testing method, namely by using a series of case experiments on functions that have been built both from the admin and user side. The output results provided were as expected and there were no errors or output that was outside of what was expected.